Direct writing of three-dimensional Cu-based thermal flow sensors using femtosecond laser-induced reduction of CuO nanoparticles. (5th April 2017) - Arakane, S; Mizoshiri, M; Sakurai, J; Hata, S
Abstract: We have demonstrated the fabrication of two types of thermal flow sensors with Cu-rich and Cu2 O-rich microheaters using femtosecond laser-induced reduction of CuO nanoparticles. The microheaters in the shape of microbridge structures were formed to thermally isolate from the substrates by four layer-by-layer laminations of two-dimensional micropatterns. First, we evaluated the patterning properties such as dispensing coating conditions and degree of reduction for the selective fabrication of three-dimensional Cu-rich and Cu2 O-rich microstructures. Then, a hot-film flow sensor with a Cu-rich microheater and a calorimetric flow sensor with a Cu2 O-rich microheater were fabricated using their respective appropriate laser irradiation conditions. The hot-film sensor with the Cu-rich microbridge single heater enabled us to measure the flow rate in a wide range of 0–450 cc min −1 . Although a large temperature dependence of the Cu2 O-rich microbridge heaters caused a large error for the hot-film flow sensors with single heaters, they showed higher heat-resistance and generated heat with a lower drive power. The temperature coefficient of resistance of the Cu2 O-rich microstructures had a semiconductor-like large absolute value and was less than  −4.6  ×  10 −8 °C −1 . The higher temperature sensitivity of the Cu2 O-rich microstructures was useful for thermal detection. Based on these advantages, a calorimetric flow sensor composed of the Cu2 O-rich microbridge single heater and two Cu2 O-rich thermal detectors was proposed and fabricated. The calorimetric flow sensor was driven by a circuit for measuring the temperature difference. The Cu2 O-rich flow sensor could detect bi-directional flow with a small output error.